Non-coding RNAs as novel biomarkers and therapeutic targets in breast cancer - Barbi, Veronica; De Martino, Sara; Aiello, Aurora; Gottardi Zamperla, Michela; Negri, Sara; Cis, Luca; Pecci, Valeria; Nanni, Simona; Farsetti, Antonella; Martelli, Fabio; Gaetano, Carlo; Atlante, Sandra (Oncology Reviews, 2025)
Breast cancer (BC) remains a leading cause of cancer-related morbidity and mortality worldwide. Its marked heterogeneity - encompassing molecular subtypes, histological characteristics, and variable therapeutic responses - continues to pose persistent clinical challenges Although advances in surgery, hormone therapy, chemotherapy, and targeted therapies have significantly improved patient outcomes, issues such as therapeutic resistance and disease relapse are still common, underscoring the need for novel molecular targets. Within this context, non-coding RNAs (ncRNAs) have emerged as pivotal regulators of breast cancer biology and hold promise as diagnostics and therapeutic agents. These non-protein-coding RNA molecules include diverse subclasses, such as long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and small non-coding RNAs (sncRNAs), each characterized by distinct structural features and biological functions. Mounting evidence implicates ncRNAs in key oncogenic processes - such as tumor initiation, progression, metastasis, immune evasion, and treatment resistance - often in a subtype-specific manner. Importantly, ncRNA expression profiles differ significantly across BC subtypes, and their stability in body fluids underscores their potential utility in liquid biopsy-based diagnostics. This review provides an integrated overview of the multifaceted roles of ncRNAs in BC, emphasizing their mechanisms of action, contributions to tumor heterogeneity, and translational potential as both biomarkers and therapeutic targets. Understanding ncRNAs complexity and context-specific functions may pave the way toward more precise, personalized interventions for BC patients.